PEMIDANAAN BAGI NAHKODA YANG MELAKUKAN KEGIATAN MENUNDA DALAM PELAYARAN TANPA PERSETUJUAN DARI SYAHBANDAR - Juhari, Juhari (Res Nullius Law Journal, 2023)
The captain of the ship carrying out repair activities, sailing trials, loading and unloading activities at the port pool, delaying, and loading and unloading dangerous goods must obtain approval from the harbormaster. That the term delay in sailing means to hold, pull, push or stick. The formulation of the problem in this research is: how is the punishment for the captain who delays the voyage without the approval of the porter based on the Law of the Republic of Indonesia Number 17 of 2008 concerning Shipping, What are the obstacles faced by the judge in the implementation of punishment for the captain who delays the voyage without the approval of the porter based on the Law of the Republic of Indonesia Number 17 of 2008 concerning Shipping. This research method uses a normative juridical type of research, namely by reviewing/analyzing secondary data in the form of legal materials, especially primary legal materials and secondary legal materials by understanding law as a set of rules or positive norms in the legal system. an invitation that regulates human life. Results of research and data analysis: Criminal based on legal facts proven to meet the elements of Article 322, Law of the Republic of Indonesia No. 17 of 2008 concerning Shipping, stated that the Defendant Noveriyanto Bin Sugiman, was legally and convincingly proven guilty of committing the crime of “The skipper who carried out delaying activities without the approval of the harbormaster, as in the third indictment. The verdict was imposed with cumulative sanctions with fines without imprisonment, this shows that the judge complies with positive law in force in Indonesia by using the legal basis in the form of Law of the Republic of Indonesia No. 17 of 2008 concerning Shipping.